A sport ski taylored to the individual skier by finite element method - Metz, M.; Becker, W. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In recent years the modern sports ski has been developed to a complex structural element, revealing many possibilities to exert influence on its mechanical properties. In the past the range of ski types sold has shown, that models can be adjusted to match the requirements of special styles of riding by fitting the parameters of design. Using computational methods it is even possible to adapt skis to the individual! skier to get an even better performance.